THE PSYCHOLOGICAL IMPACTS OF WAR ON MAIN CHARACTER: A FREUDIAN PERSPECTIVE ON "GRAVE OF THE FIREFLIES" - Hendrilin, Darwin; Margawati, Prayudias (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2024)
This study uses Freud's psychoanalysis to examine the psychological growth of the main character. in Akiyuki Nosaka's story Grave of the Fireflies. The writer examines the dynamic interaction of Freud's tripartite model the id, ego, and super-ego by analyzing the choices and actions of the characters. Every element of the main character's tripartite the Id, Ego, and Super-ego is identified and explained in the novel with the use of the qualitative technique. The results demonstrate that when the character strives to get some nourishment for himself and his sister, his id is clearly visible. The ego can be seen in his efforts to make rational decisions and find the best ways to protect himself and his sister. A clear example of the influence of the super-ego is his feelings of guilt and regret over some of his decisions, such as not returning to his aunt o refusing to seek further help from others. The analysis reveals how war impacts the psychological states of individuals, highlighting the internal conflicts that arise when basic survival needs overshadow ethical standards.